2022
DOI: 10.22271/23487941.2022.v9.i4a.621
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal efficacy of ornamental fishes to control Aedes aegypti in West Bengal

Abstract: Escalating population of Aedes aegypti may lead to cause Dengue. However, controlling their larvae by using conventional techniques like insecticides, mosquito repellents are hazardous for human health and environment. Hence, it is recommended to biologically control the mosquito larvae through ornamental fish as they are eco-friendly and cost effective. In the present study, consumption rate of Aedes aegypti larvae and other food preference of six fishes (Angel fish, Betta fish, Gold fish, Red swordtail, Moll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…In the laboratory, these fish species are used to reduce the number of mosquito larvae. The present findings are consistent with those of earlier research reports in various ecosystems conducted by Datta et al, 2022 [29] ; Tilak et al, 2007 [26] ; Câmara et al, 2017 [27] ; Sumithra et al, 2014 [28] and Gupta et al, 2009 [30] . The results of the present study make it clear that all four species of fish prefer live food, particularly mosquito larvae, than artificial food, and that this preference is substantially greater than that of other fish species (Table-3; Table-5; Fig- 5; Fig- 6).…”
Section: Discussionsupporting
confidence: 93%
“…In the laboratory, these fish species are used to reduce the number of mosquito larvae. The present findings are consistent with those of earlier research reports in various ecosystems conducted by Datta et al, 2022 [29] ; Tilak et al, 2007 [26] ; Câmara et al, 2017 [27] ; Sumithra et al, 2014 [28] and Gupta et al, 2009 [30] . The results of the present study make it clear that all four species of fish prefer live food, particularly mosquito larvae, than artificial food, and that this preference is substantially greater than that of other fish species (Table-3; Table-5; Fig- 5; Fig- 6).…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies [26] suggested that ornamental fishes specially Gold fish exhibit excellent larvivorous potentials to control mosquito population. Recently in our laboratory similar findings [23,24] were well documented. Furthermore, Mannaa et al, (2008) [27] in his observation suggested that Poecilia reticulata can consume 65-84 IV instar Culex larvae in a period of 3 hours.…”
Section: Discussionsupporting
confidence: 82%
“…30 For a fish to be used as a mosquito biocontrol agent, it must meet two basic criteria: First, it must have a high predation efficacy on mosquito larvae; second, it must be resistant to low oxygen concentrations while also being toxic metabolite tolerant. 31 In future research, it is expected that the potential of rosy barb fish needs to be tested on other species of mosquito larvae. Larvivorous fish for Aedes aegypti in the field are still rarely found.…”
Section: Discussionmentioning
confidence: 99%